Anti-inflammatory activity of an ethanolic Caesalpinia sappan extract in human chondrocytes and macrophages - Shengqian Q. Wu (2018)
Ethnopharmacological relevance: Caesalpinia sappan is a common remedy in Traditional Chinese Medicine and possesses diverse biological activities including anti-inflammatory properties. Osteoarthritis (OA) is a degenerative joint disease with an inflammatory component that drives the degradation of cartilage extracellular matrix. In order to provide a scientific basis for the applicability of Caesalpinia sappan in arthritic diseases, the present study aimed to assess the effects of an ethanolic Caesalpinia sappan extract (CSE) on human chondrocytes and macrophages. Materials and methods: Primary human chondrocytes were isolated from cartilage specimens of OA patients. Primary cells, SW1353 chondrocytes and THP-1 macrophages were serum-starved and pretreated with different concentrations of CSE prior to stimulation with 10 ng/ml of interleukin-1beta (IL-1β) or lipopolysaccharide (LPS). Following viability tests, nitric oxide (NO) and tumor necrosis factor-alpha (TNF-α) were evaluated by Griess assay and ELISA, respectively. Using validated real-time PCR assays, mRNA levels of IL-1β, TNF-α, inducible nitric oxide synthase (iNOS), and cyclooxygenase-2 (COX-2) were quantified. SW1353 cells were cotransfected with a COX-2 luciferase reporter plasmid and nuclear factor-kappa-B (NF-κB) p50 and p65 expression vectors in the presence or absence of CSE. Results: CSE dose-dependently inhibited the expression of pro-inflammatory cytokines IL-1β and TNF-α in IL-1β-stimulated chondrocytes and LPS-stimulated THP-1 macrophages. CSE further suppressed the synthesis of NO in primary OA chondrocytes by blocking iNOS mRNA expression. The inhibition of COX-2 transcription was found to be related with the CSE inhibition of the p65/p50-driven transactivation of the COX-2 promoter. Conclusions: The present report is first to demonstrate the anti-inflammatory activity of CSE in an in vitro cell model of joint inflammation. CSE can effectively abrogate the IL-1β-induced over-expression of inflammatory mediators at the transcriptional level in human chondrocytes and macrophages, most likely by inhibiting NF-κB (p65/p50) signaling. Blockade of IL-1β-induced NF-κB signaling and its downstream pro-inflammatory targets by CSE may be beneficial for reducing cartilage breakdown in arthritis. © 2011 Elsevier Ireland Ltd. All rights reserved.